Lobule separator prosthesis to prevent adhesion of reconstructed ear lobe - Lokendra Gupta; Parul Pujary; Priyanka Agarwal (Wolters Kluwer Medknow Publications, 2016)
An adhesion is a band of scar tissue that binds two parts of the tissue together, which develops when the body's repair mechanisms respond to any tissue disturbance, such as surgery, infection, trauma, or radiation. Prevention of unwanted scar bands is of utmost importance to develop esthetic and healthy tissue. This article describes a technique to prevent the adhesion of the surgically reconstructed ear lobule with facial skin, using novel lobule separator prosthesis.